Role of public administration in promoting sociopolitical development - De Leon, Corazon Alma G. (Philippine Journal of Public Administration, 1998)
Public administration plays an intricate role in promoting sociopolitical development. At the center of the exposition is the argument that good public administration or governance is a necessary ingredient for development. As the Philippine seeks to achieve a high level of sociopolitical development, the Philippine civil service should therefore be reformed to further enhance its capability in advancing sociopolitical goals.